Investigation of Iran’s Educational Structure during Qajar Era - Yousefvand, Reza; Hormoz, Jila Rostami; Begdeli, Mohsen (Journal of History Culture and Art Research, 2018)
During Qajar era, just like the earlier eras, the pedagogy was not provided to the public. The nobles and aristocrats used to appoint a tutor and most of talented and clever students have been deprived from pedagogy because of inadequate number of schools. This era is considered as the era of cultural changes and people movements. The era is also known as the era of passing from pre-modernistic Iran to developed Iran. Given the increased relations between Iran and Europe and construction of schools and sending students to Europe, different sciences were gradually propagated in Iran. Abbas Mirza imitated intentionally the similar corrective process devised in Ottoman Empire during Sultan Selim III sovereignty and started a military corrective plan entitled new system including introduction of European military technology and new methods of training soldiers. Thereby, other measures started to be taken including sending over students to overseas, translation of European books, establishment of print house, newspaper publish and other than these developments and changes made Iran shortcomings to become clear against Europe. Therefore, the first steps for education system development were taken in this era by Abbas Mirza and Ghaem Magham Farahani and followed by Mirza Taghi khan Amir Kabir. Thereby, the preliminary stages of modern era were taken.